Case Study: Efficacy of Engineering Controls in Mitigating Diacetyl and 2,3-Pentanedione Emissions During Coffee Grinding - Stanton, Marcia L.; McClelland, Tia L.; Beaty, Michael; Ranpara, Anand; Martin, Stephen B. (Frontiers in Public Health, 2022)
Exposure to elevated levels of diacetyl in flavoring and microwave popcorn production has been associated with respiratory impairment among workers including from a severe lung disease known as obliterative bronchiolitis. Laboratory studies demonstrate damage to the respiratory tract in rodents exposed to either diacetyl or the related alpha-diketone 2,3-pentanedione. Respiratory tract damage includes the development of obliterative bronchiolitis-like changes in the lungs of rats repeatedly inhaling either diacetyl or 2,3-pentanedione. In one flavored coffee processing facility, current workers who spent time in higher diacetyl and 2,3-pentanedione areas had lower lung function values, while five former flavoring room workers were diagnosed with obliterative bronchiolitis. In that and other coffee roasting and packaging facilities, grinding roasted coffee beans has been identified as contributing to elevated levels of diacetyl and 2,3-pentanedione. To reduce worker exposures, employers can take various actions to control exposures according to the hierarchy of controls. Because elimination or substitution is not applicable to coffee production facilities not using flavorings, use of engineering controls to control exposures at their source is especially important. This work demonstrates the use of temporary ventilated enclosures around grinding equipment in a single coffee roasting and packaging facility to mitigate diacetyl and 2,3-pentanedione emissions from grinding equipment to the main production space. Concentrations of diacetyl and 2,3-pentanedione were measured in various locations throughout the main production space as well as inside and outside of ventilated enclosures to evaluate the effect of the enclosures on exposures. Diacetyl and 2,3-pentanedione concentrations outside one grinder enclosure decreased by 95 and 92%, respectively, despite ground coffee production increasing by 12%, after the enclosure was installed. Outside a second enclosure, diacetyl and 2,3-pentanedione concentrations both decreased 84%, greater than the 33% decrease in ground coffee production after installation. Temporary ventilated enclosures used as engineering control measures in this study effectively reduced emissions of diacetyl and 2,3-pentanedione at the source in this facility. These findings motivated management to explore options with a grinding equipment manufacturer to permanently ventilate their grinders to reduce emissions of diacetyl and 2,3-pentanedione.